The hundred dresses : the most iconic styles of our time - McKean, Erin (Bloomsbury, 2013)
Presents a visual A-to-Z reference profiling iconic vintage and modern dresses, combining evocative illustrations with assessments of each depicted style, their famous wearers, and typical accessories.